Responding to the Unique Complexities of Fetal Alcohol Spectrum Disorder - Flannigan, Katherine; Pei, Jacqueline; McLachlan, Kaitlyn; Harding, Kelly; Mela, Mansfield; Cook, Jocelynn; Badry, Dorothy; McFarlane, Audrey (Frontiers in Psychology, 2022)
Fetal alcohol spectrum disorder (FASD) is a multifaceted disability, characterized not only by brain- and body-based challenges, but also high rates of environmental adversity, lifelong difficulties with daily living, and distinct sociocultural considerations. FASD is one of the most common neurodevelopmental disabilities in the Western world and associated with significant social and economic costs. It is important to understand the complexities of FASD and the ways in which FASD requires unique consideration in research, practice, and policy. In this article, we discuss our perspectives on factors that distinguish FASD from other disabilities in terms of complexity, co-occurrence, and magnitude. We provide an overview of select literature related to FASD as a socially rooted disability with intergenerational impacts and multiple layers of stigma. These social issues are intertwined with notable experiences of adversity across the lifespan and high rates of co-occurring health concerns for individuals with FASD, all of which present unique challenges for individuals, caregivers, families, service providers, and policy makers. Understanding these factors is the first step in developing and implementing specialized initiatives in support of positive outcomes for individuals with FASD and their families. Future directions are proposed for advancing research, practice, and policy, and responding to the unique complexities of FASD.